2018
DOI: 10.2196/periop.7874
|View full text |Cite
|
Sign up to set email alerts
|

Accessible Communication Tools for Surgical Site Infection Monitoring and Prevention in Joint Reconstruction: Feasibility Study

Abstract: Background The National Surgical Quality Improvement Program logs surgical site infections (SSIs) as the most common cause of unplanned postoperative readmission for a variety of surgical interventions. Hospitals are making significant efforts preoperatively and postoperatively to reduce SSIs and improve care. Telemedicine, defined as using remote technology to implement health care, has the potential to improve outcomes across a wide range of parameters, including reducing SSIs. Ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Other researchers have developed an app to monitor wound recovery using mobile phone technology [ 30 , 31 ]. It has also been shown by Lu et al [ 32 ] that adherence with pre- and postoperative protocols for reducing surgical site infections can be increased using simple automated messaging systems. These examples illustrate the perceived potential for mobile phone technology in the perioperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have developed an app to monitor wound recovery using mobile phone technology [ 30 , 31 ]. It has also been shown by Lu et al [ 32 ] that adherence with pre- and postoperative protocols for reducing surgical site infections can be increased using simple automated messaging systems. These examples illustrate the perceived potential for mobile phone technology in the perioperative period.…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, however, we consider the studies that explicitly indicate better communication flow between actors. For example, Lu et al [80] described the development and implementation of two software applications that generate automated text messages and phone calls with the aim of regularly reminding patients about the preoperatory procedures and monitoring signs and symptoms of SSIs postoperatively. As a result, patients felt more confident by receiving medical advice on a regular basis, while nurses and surgeons are efficient with monitoring patients' outcomes based on auto-generated reports, without an increased workload [80].…”
Section: Experiential/hedonic Valuementioning
confidence: 99%
“…For example, Lu et al [80] described the development and implementation of two software applications that generate automated text messages and phone calls with the aim of regularly reminding patients about the preoperatory procedures and monitoring signs and symptoms of SSIs postoperatively. As a result, patients felt more confident by receiving medical advice on a regular basis, while nurses and surgeons are efficient with monitoring patients' outcomes based on auto-generated reports, without an increased workload [80]. Similarly, other studies reported that patients appreciate the direct connection with nurses and physicians via smartphone applications, demonstrating more interest in interacting with these professionals and asking questions about wound treatments, medications, and medical appointments [75,84].…”
Section: Experiential/hedonic Valuementioning
confidence: 99%